NAV Premiums in Listed Swedish Property Companies : Idiosyncratic and Systematic Factors Affecting the NAV Premium - Lemmetty, Tatu (My University, 2022)
The NAV puzzle phenomenon refers to the differentiation of companies’ or funds’ net asset value and market capitalization. The differentiation in NAV and market capitalization have been explained by several idiosyncratic company specific as well as systematic market wide factors in previous literature. This thesis enlightens the phenomenon in listed Swedish property companies with an aim find out whether they trade at a NAV premium or NAV discount. In addition, different factors and their effect on the NAV puzzle are tested and four models, consisting of different combinations of the factors, are built to explain the NAV puzzle. The data consists of overall 27 listed Swedish property companies from 2010 to 2020. The models as well as different factors’ effect on NAV premiums are tested with an OLS-regression. Of the factors size, return, investments abroad, time to maturity for interest bearing debt, vacancy, market average premium, credit spread, and term spread have the same effect on NAV premiums as previous studies suggest. Only leverage, risk, property-type diversification, and liquidity coefficients have an opposite sign as suggested by the literature. However, of these only liquidity’s coefficient is statistically significant. Models 1, 2 and 3, consisting of idiosyncratic company specific factors, explain from 23% up to 27% of the NAV premiums, whilst the 4th model, consisting of all factors taken into account in this study, explains 31% of the NAV premiums. The first models are in line with previous studies, but the 4th model’s explanatory power falls a bit short compared to studies made in the U.K. stock markets. Overall, the results in NAV premiums in Swedish listed property companies are quite in line with previous studies mostly made in the U.K and other European stock markets. The slight deviation in the explanatory power of the 4th model compared to similar studies might be due to the fact that in Sweden most of the property companies have a high degree of development activities, which is not controlled for by the factors in this study.

Nettovarallisuuspreemio viittaa siihen, että yhtiön tai rahaston markkina-arvo on suurempi kuin nettovarallisuus. Tätä eroavaisuutta on selitetty aiemmissa tutkimuksissa useilla niin yrityskohtaisilla kuin systemaattisilla markkinatasonkin faktoreilla. Tämä tutkielma tutkii ilmiötä ruotsalaisilla listatuilla kiinteistösijoitusyhtiöillä tavoitteenaan pyrkiä selvittämään, että käydäänkö kyseisillä yhtiöillä keskimäärin kauppaa preemiolla vai alennuksella. Lisäksi tutkitaan yksittäisten eri faktoreiden vaikutusta ilmiöön sekä selvitetään kuinka paljon eroavaisuudesta pystytään eri faktoreista muodostetuilla malleilla selittämään. Tutkielman data kattaa yhteensä 27 ruotsalaista listattua kiinteistösijoitusyhtiötä vuodesta 2010 vuoteen 2020. Malleja sekä yksittäisiä faktoreita testataan PNS-menetelmää käyttäen. Faktoreista koko, tuotto, investoinnit ulkomaille, hajautus, korollisen velan keskimääräinen maturiteetti, vajaakäyttöaste, markkinoiden keskimääräinen preemio, luottoriski sekä pitkien ja lyhyiden korkojen tuottoero vaikuttivat nettovarallisuuspreemioon kuten ennakoitiin aiempiin tutkimuksiin peilaten. Vain velkaisuus, riski ja likviditeetti vaikuttivat eri suuntaisesti nettovarallisuuspreemioon, ja näistäkin kolmesta ainoastaan likviditeetillä oli tilastollisesti merkitsevä kerroin. Malleista 1 ja 2, jotka koostuivat yrityskohtaisista faktoreista, selittivät 23%-27% nettovarallisuuspreemiosta, kun taas neljäs malli, joka sisälsi kaikki faktorit, selitti 31%. Yrityskohtaisista muuttujista kootut mallit olivat linjassa aiemman kirjallisuuden kanssa, mutta neljännen mallin selitysaste jäi hieman vastaavista tutkimuksista Ison-Britannian markkinoilta. Kokonaisuudessaan nettovarallisuuspreemioon vaikuttavat faktorit sekä mallit ovat yhteneviä eri markkinoilla, suurimmaksi osaksi Iso-Britanniassa ja muissa Euroopan maissa, tehtyjen aiempien tutkimusten kanssa. Neljännen mallin hieman vajavainen selitysaste aiempiin tutkimuksiin verrattuna selittynee sillä, että ruotsalaisista listatuista kiinteistöyrityksistä suuri osa harrastaa myös kiinteistökehitystoimintaa pelkän kiinteistöinvestointitoiminnan lisäksi, jota ei tutkimuksessa mukana olevilla faktoreilla pystytä kontrolloimaan.
Keywords: listed real estate, net asset value spread, NAV premium